Weak links between exports and economic growth in Latin America and the Caribbean - Mulder, Nanno (UN ECLAC SantiagoCL, 2009)
Analyses the characteristics of the region's export development over the past two decades and the reasons why spillovers to structural change and economic growth have remained limited.